Optimizing spinal cord injury care in Canada: Development of a framework for strategy and action - Rivera, Joanna Marie B.; Yousefi, Charlene; Cheng, Christiana L.; Norman, Cameron D.; Legare, Jeanne; McFarlane, Alana; Noonan, Vanessa K. (Frontiers in Public Health, 2022)
National health strategies are integral in defining the vision and strategic direction for ensuring the health of a population or for a specific health area. To facilitate a national coordinated approach in spinal cord injury (SCI) research and care in Canada, Praxis Spinal Cord Institute, with support from national experts and funding from the Government of Canada, developed a national strategy to advance SCI care, health, and wellness based on previous SCI strategic documents. This paper describes the development process of the SCI Care for Canada: A Framework for Strategy and Action. Specifically, it covers steps from reviewing previous SCI strategic planning documents to build on existing work through to community co-creation and the plans for communication, dissemination, and evaluation. The SCI Care Strategic Framework promotes an updated common understanding of the goals and vision of the SCI community, as well as strengths and priorities within the SCI system regarding care, health, and wellness. Additionally, it supports the coordination and scaling up of SCI advancements to make a sustainable impact nationwide focusing on the needs of people living with SCI.